UU PORNOGRAFI DALAM PERSPEKTIF HUKUM ISLAM (Mazahib, 2012)
Pornography is like an octopus that plagued the whole society. Background of many factors, among others, women's fashions, the media, including internet. Various regulations were issued to mute it. Still can not stem its spread. Pornography is located between the ethical and aesthetic dimensions. Talk about moral ethics, aesthetics are talking about the beauty of Islamic law has its own rules of procedure and ethics association of dress.